Ferroptosis triggers mitochondrial fragmentation via Drp1 activation - Lohans Pedrera; Laura Prieto Clemente; Alina Dahlhaus; Sara Lotfipour Nasudivar; Sofya Tishina; Daniel Olmo González; Jenny Stroh; Fatma Isil Yapici; Randhwaj Pratap Singh; Nils Grotehans; Thomas Langer; Ana J. García-Sáez; et al. (Cell Death and Disease)
Abstract Constitutive mitochondrial dynamics ensure quality control and metabolic fitness of cells, and their dysregulation has been implicated in various human diseases. The large GTPase Dynamin-related protein 1 (Drp1) is intimately involved in mediating constitutive mitochondrial fission and has been implicated in mitochondrial cell death pathways. During ferroptosis, a recently identified type of regulated necrosis driven by excessive lipid peroxidation, mitochondrial fragmentation has been observed. Yet, how this is regulated and whether it is involved in ferroptotic cell death has remained unexplored. Here, we provide evidence that Drp1 is activated upon experimental induction of ferroptosis and promotes cell death execution and mitochondrial fragmentation. Using time-lapse microscopy, we found that ferroptosis induced mitochondrial fragmentation and loss of mitochondrial membrane potential, but not mitochondrial outer membrane permeabilization. Importantly, Drp1 accelerated ferroptotic cell death kinetics. Notably, this function was mediated by the regulation of mitochondrial dynamics, as overexpression of Mitofusin 2 phenocopied the effect of Drp1 deficiency in delaying ferroptosis cell death kinetics. Mechanistically, we found that Drp1 is phosphorylated and activated after induction of ferroptosis and that it translocates to mitochondria. Further activation at mitochondria through the phosphatase PGAM5 promoted ferroptotic cell death. Remarkably, Drp1 depletion delayed mitochondrial and plasma membrane lipid peroxidation. These data provide evidence for a functional role of Drp1 activation and mitochondrial fragmentation in the acceleration of ferroptotic cell death, with important implications for targeting mitochondrial dynamics in diseases associated with ferroptosis.